Broad-Based CD4+ T Cell Responses to Influenza A Virus in a Healthy Individual Who Lacks Typical Immunodominance Hierarchy - Chen, Li; Anthony, Anjaleena; Oveissi, Sara; Huang, Miaojuan; Zanker, Damien; Xiao, Kun; Wu, Chao; Zou, Quanming; Chen, Weisan (Frontiers in Immunology, 2017)
Influenza A virus (IAV) infection is a significant cause of morbidity and mortality worldwide. CD4+ T cell responses have been shown to be important for influenza protection in mouse models and in human volunteers. IAV antigen-specific CD4+ T cell responses were found to focus on matrix 1 (M1) and nucleoprotein (NP) at the protein antigen level. At the epitope level, only several epitopes within M1 and NP were recognized by CD4+ T cells. And the epitope-specific CD4+ T cell responses showed a typical immunodominance hierarchy in most of the healthy individuals studied. In this study, we reported one case of atypical immunodominance hierarchy of CD4+ T cell responses to IAV. M1 and NP were still the immunodominant targets of CD4+ T cell responses. However, CD4+ T cell responses specific to eleven epitopes derived from M1 and NP were detected and showed no significant immunodominance hierarchy. Such an atypical pattern is likely determined by the individual’s HLA alleles. These findings will help us better understand the anti-IAV immunity as a whole and improve future vaccines against IAV.